Imaging of vitamin D in psoriatic skin using time-of-flight secondary ion mass spectrometry (ToF-SIMS): A pilot case study. Issue 189 (May 2019) - Siekkeri Vandikas, Maria; Hellström, Evelina; Malmberg, Per; Osmancevic, Amra
Highlights: The relationship between serum vitamin D and the severity of psoriasis remains contradictory. Serum vitamin D might not reflect the amount of available and hormonally active vitamin D in the skin. There is a need to study the autocrine and paracrine effects of vitamin D directly in the psoriatic skin. ToF-SIMS can be used to study vitamin D in skin biopsies, obtaining both spatial and semi-quantitative information. Abstract: Recently it has been recognized that there is a need of investigating in detail the vitamin D synthesis and metabolism directly in the skin with respect to its possible autocrine and paracrine actions. The potential effects the active metabolite of vitamin D exerts in pathological skin conditions like psoriasis needs to be clarified. Under ultraviolet B (UVB) irradiation skin can autonomously synthesize, activate and degrade vitamin D. In this pilot case study, we used for the first time Time-of-flight secondary ion mass spectrometry (ToF-SIMS) in the analysis of skin biopsies from a patient with psoriasis before and after UVB phototherapy. We were able to visualize vitamin D3 and its metabolites in the skin and subcutaneous tissue. At the same time information about their localization at subcellular level and morphology of the skin was received. This study proves that ToF-SIMS is a promising powerful tool to be used when investigating vitamin D´s role in dermatological diseases through skin biopsies.